2019
DOI: 10.1371/journal.pone.0219777
|View full text |Cite|
|
Sign up to set email alerts
|

A controlled-release oral opioid supports S. aureus survival in injection drug preparation equipment and may increase bacteremia and endocarditis risk

Abstract: Background Injection drug use-associated endocarditis (IDUaIE) incidence in Ontario has recently been associated with hydromorphone prescribing rates. Staphylococcus aureus causes the majority of cases of IDUaIE in Ontario and across North America. Hydromorphone controlled-release (Hydromorphone-CR) requires a complex technique for injection and therefore provides multiple opportunities for contamination. Hydromorphone-CR contains several excipients, which could enhance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 30 publications
0
37
0
Order By: Relevance
“…Our population-wide study in Ontario with over 60,000 PWID showed a 3.3 fold higher risk of acquiring IE within 120 days when prescribed hydromorphone-CR compared with other opioids (p<0.0001) (24). Moreover, we have also shown that drug excipients within hydromorphone-CR preserve S. aureus survival in vitro (12). This was not the case for immediate release hydromorphone or controlled-release Oxycodone (12).…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Our population-wide study in Ontario with over 60,000 PWID showed a 3.3 fold higher risk of acquiring IE within 120 days when prescribed hydromorphone-CR compared with other opioids (p<0.0001) (24). Moreover, we have also shown that drug excipients within hydromorphone-CR preserve S. aureus survival in vitro (12). This was not the case for immediate release hydromorphone or controlled-release Oxycodone (12).…”
Section: Discussionmentioning
confidence: 70%
“…This was not the case for immediate release hydromorphone or controlled-release Oxycodone (12). Furthermore, we found that the injectate obtained from aspirating from equipment previously used to inject hydromorphone-CR was contaminated with S. aureus in 14% of cases and thus injection of this drug would commonly be associated with bacteremia (12). The protective effect of using a lighter to pulverize drugs in this study may reflect a greater likelihood of heating preparations prior to injection due to the accessibility to a heating source.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations